2013
DOI: 10.3758/s13414-013-0540-z
|View full text |Cite
|
Sign up to set email alerts
|

Amodal completion is modulated by lightness similarity

Abstract: The strength of amodal completion is known to be modulated by contour relationships and global shape. Some researchers have shown that amodal completion also depends on surface similarity, but they have not distinguished the relative importance of similarity in surface representations either pre or post lightness constancy. In the experiments reported here, we aimed to determine whether amodal completion depends on processes that occur either before or after the establishment of lightness constancy. We used co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…These basic findings already show that amodal completion can be influenced by the visible colours in the occlusion pattern. In addition, these results are consistent with previous findings that surface characteristics, more specifically colour, play a role in amodal completion (Dadam et al, 2012;Kim et al, 2014;Pinna, 2008;Su et al, 2010;Yin et al, 1997). Next, we proposed an analysis in which we had a closer look at the net effect of colour context, i.e., the colour context analyses.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These basic findings already show that amodal completion can be influenced by the visible colours in the occlusion pattern. In addition, these results are consistent with previous findings that surface characteristics, more specifically colour, play a role in amodal completion (Dadam et al, 2012;Kim et al, 2014;Pinna, 2008;Su et al, 2010;Yin et al, 1997). Next, we proposed an analysis in which we had a closer look at the net effect of colour context, i.e., the colour context analyses.…”
Section: Discussionsupporting
confidence: 87%
“…Using displays with illusory colours, Pinna (2008) showed that amodal completion could also be modulated by perceived colours and that they could even prevent completion to occur (which happened when the perceived colours suggested a hole instead of an occluder). More recently, Kim, Jeng, and Anderson (2014) studied the influence of lightness similarity, showing modulating effects of perceived surface similarities, e.g., after accounting for the effect of shadows on the visible contour fragments. A study that explicitly focused on the perceived surface characteristics behind the occluder was performed by Yin, Kellman, and Shipley (1997) who constructed stimuli to isolate surface colour completion from boundary completion.…”
mentioning
confidence: 99%
“…In conflict with these two stimulus-driven accounts, amodal completion seems not solely influenced by low-level stimulus configurations but also impacted by various high-level contextual cues, as demonstrated in several studies. These cues encompass factors such as lighting conditions ( Kim, Jeng, & Anderson, 2014 ), spatial context ( Rauschenberger, Peterson, Mosca, & Bruno, 2004 ), temporal context ( Plomp & van Leeuwen, 2006 ), task demands ( Lee & Vecera, 2005 ), and familiarity with material properties ( Gerbino & Zabai, 2003 ; Vrins, de Wit, & van Lier, 2009 ) and object shapes ( Hazenberg & van Lier, 2016 ; Yun, Hazenberg, & van Lier, 2018 ). Moreover, research has shown that explicit learning can influence the preferred completion for occlusion patterns, especially in cases where local and global cues conflict ( Hazenberg, Jongsma, Koning, & van Lier, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The visual system’s incorporation of such hidden visual information into its 3-dimensional representation of the objects in a scene is called amodal completion [1]. Previous studies have been concerned with the stimulus conditions necessary for amodal completion, including good continuation [2], luminance similarity [3], and shape similarity [4]. Other researchers have shown that amodal completion can be affected by top-down influences entailing knowledge of the partially occluded objects [5,6].…”
Section: Introductionmentioning
confidence: 99%